Strengthen Primary Health Care for Neonatal Survival and Child Health in India: A Review - Chandrakant Lahariya; Animesh Jain; Aninda Debnath; B. Shantharam Baliga; Matthew A. Manoj (Preventive Medicine: Research & Reviews)
This review examines the current landscape of neonatal and child health and how primary healthcare system and primary care physicians can contribute to improved Newborn & child survival and health. The article draws on an analysis of global and national strategies such as the India Newborn Action Plan, Ayushman Bharat’s Health and Wellness Centres (HWCs) and the role of community in health services. The review identifies the need for integrated nutrition services, robust health information systems and community engagement. Key initiatives include the transformation of primary health centres into HWCs, the deployment of Community Health Officers to deliver newborn and child health interventions and the leveraging of digital tools, including artificial intelligence and information technology, for preventive care and monitoring.